Renewal of Islamic Law Munawir Sjadzali's Perspective and Its Implementation in Analyzing Bank Interest Law - Yusron, Pandi; Ridwan,; Supani,; Ismail, Faisal Husen (Advances in Humanities and Contemporary Studies, 2024)
Islamic law reform has always been an interesting topic to discuss. No exception is the reform of Islamic law carried out by Munawir Sjadzali. His idea of reform was expressed in the idea of re-actualizing Islamic law, which was the result of his anxiety about the ambivalent attitude of Indonesian Muslims regarding religious beliefs and practices which, according to him, were incompatible. Ijtihad for the re-actualization of Islamic law is generally based on ushul fiqh theories such as naskh, 'urf, and maṣlaḥat. This study analyzes the ijtihad paradigm of re-actualization of Islamic law as a representation of the reform of Islamic law in Indonesia and then analyzes an issue regarding bank interest. The research method used is qualitative with the type of library research. The collected data was analyzed normatively using a historical and ushul fiqh approach. This research shows that the naskh argument put forward by Munawir to build the concept of ijtihad is not strong. Likewise with the theory of benefits that he uses. As for bank interest, the opinion can be accepted that the application of the riba verse to bank interest is seen as inappropriate. There is a different character between the interest system applied in banking and the character of debt which attracts benefits (qarḍ jarra manfa'atan).